Public Infrastructure Development and Government-toGovernment Agreements: Scopes and Opportunities - Villafranqui Rivera, Giancarlo (2020)
One of the key factors to improve the competitiveness of a country is the development of public infrastructure, which promotes growth and allows its sustainability, but its execution must be planned and adapted to current and future needs in order to provide quality to a growing universe of users. The State-to-State contracting mechanism provides us with an additional alternative for the timely execution of public investment projects. It will be the responsibility of the State to correctly manage its use so that the solution does not become a problem.